2020
DOI: 10.3390/sym12111899
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Internal Gravity Waves Far from Moving Non-Local Source

Abstract: We consider analytical solutions describing the generation of internal gravity waves far from a non-local source of disturbances. We suppose that the source moves on the surface of stratified medium of a finite depth. A model distribution of the non-local source shape with radial symmetry is used. This approximation correctly describes (qualitatively) the main spatiotemporal characteristics of natural sources of generation of internal gravity waves in the ocean. The resulting solution is the sum of wave modes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…pycnic elevation, the velocity components, the density, and the pressure) can be determined; a certain initial spatial distribution of these components can be specified [6][7][8]. Far from the perturbation sources, assuming the adequacy of using the linear wave dynamics model, the far fields of internal gravity waves can be calculated from the asymptotic formulas; in this case, as shown by the calculation results, under the majority of real hydrological conditions of the World Ocean the basic contribution to the far fields is made only by first several wave modes [3,4,[16][17][18].…”
Section: Results Of the Numerical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…pycnic elevation, the velocity components, the density, and the pressure) can be determined; a certain initial spatial distribution of these components can be specified [6][7][8]. Far from the perturbation sources, assuming the adequacy of using the linear wave dynamics model, the far fields of internal gravity waves can be calculated from the asymptotic formulas; in this case, as shown by the calculation results, under the majority of real hydrological conditions of the World Ocean the basic contribution to the far fields is made only by first several wave modes [3,4,[16][17][18].…”
Section: Results Of the Numerical Calculationsmentioning
confidence: 99%
“…To carry out estimative calculations of internal gravity waves it is necessary to select the parameters of the used source model so that to approximate the modeled wave systems to those observed in reality including the space photos and wave patterns [12][13][14]. Thus, the mathematical models of wave generation can be not only verified but also used to carry out the predictive estimations since these model conditions specified a priori contain a lot of real information on whose base the linear theory can give satisfactory results far from various perturbation sources [3,4,[15][16][17][18].…”
mentioning
confidence: 99%
“…Recently, a number of researchers have focused their attention to investigate the dynamics of IGWs in different contexts. To mention a few, Bulatov et al [14] have shown that the IGWs can be generated far from a non-local source of disturbances in a layer of stratified media of a finite depth. The theory of AGWs was revisited by Chatterjee et al [11] to study the nonlinear coupling of AGWs and IGWs by taking into account the effects of the Coriolis force both in the contexts of the Zakharov approach [15] and the wave kinetic theory approach [16], [17].…”
Section: Introductionmentioning
confidence: 99%